Application of PCR-based diagnostic tools that target Enterocytozoon hepatopenaei for the molecular detection of a Vittaforma-like microsporidium that infects Penaeus vannamei from Costa Rica - Nelson Pena-Navarro (2023)
Several PCR methodologies are available for the detection of Enterocytozoon hepatopenaei (EHP) that target the SSU rRNA gene. However, these methodologies are reported as unsuitable for the detection of EHP due to specificity issues. Here, we report the applicability of two commonly used SSU rRNA methodologies for the detection of additional microsporidia from the genus Vittaforma that is present in cultured Penaeus vannamei from Costa Rica. The molecular detection of DNA of the novel microsporidia can only be achieved using SSU rRNA targeting methodologies and does not cross-react with the highly specific spore wall protein gene PCR detection method.